(untitled) (The Review of Diabetic Studies, 2024)
Background Healthcare-associated infections (HAIs) affect 5-15% of hospitalized patients in high-income countries and up to 25% in low- and middle-income settings, driving excess mortality, antimicrobial resistance, and substantial costs. These infections span device-associated (e.g., CLABSIs, CAUTIs), surgical site infections, and those in ICUs, long-term care, and ambulatory settings, underscoring the need for integrated, multimodal infection prevention and control (IPC) strategies combining systems thinking, behavioral science, and evidence-based bundles.​ Methods This review synthesizes evidence from systematic reviews, meta-analyses, point prevalence surveys, and implementation studies on multimodal IPC interventions, including WHO’s eight core components, hand hygiene campaigns, device bundles, surveillance-feedback loops, and human factors approaches. It addresses HAI epidemiology, intervention effectiveness across settings, and frameworks for sustainability, targeting clinicians, infection preventionists, and policymakers.​ Results Multimodal strategies yield 30-60% reductions in HAIs, with bundle compliance >95% eliminating CLABSIs in some ICUs and boosting hand hygiene from <50% to >80%. Environmental innovations (e.g., UV-C disinfection) and tailored measures in high-risk populations (neonates, immunocompromised) curb MDROs and outbreaks, though barriers like staffing shortages and alert fatigue persist.​ Conclusions Integrated IPC programs, emphasizing leadership, training, and real-time feedback, sustainably lower HAIs across care continuums. Future priorities include scalable tech-AI surveillance, equity-focused research in LMICs, and de-implementation of low-value practices to achieve near-zero HAIs.​